2004
DOI: 10.1111/j.1572-0241.2004.40502.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Upper Endoscopy in the Management of Patients with Gastroesophageal Reflux Disease

Abstract: It was uncommon for an EGD to alter antireflux therapy. The management was improved in approximately one-third of the patients by dilating esophageal stricture, finding BE to initiate surveillance, or finding severe esophagitis. EGD should be performed when alarm symptoms are present, especially in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 19 publications
0
17
0
4
Order By: Relevance
“…In referral centres, about 50% of patients will have oesophagitis, but in primary care and the general population, the rate of oesophagitis is more in the range of 48 Most patients with oesophagitis have mild LA Grade A-B disease and only 10% have the more severe LA Grade C-D oesophagitis. 42 Endoscopy can also evaluate complications of GERD, such as peptic strictures and Barrett's oesophagus, and is recommended if patients have 'alarm symptoms', such as progressive dysphagia, weight loss or iron deficiency anaemia. 42 In routine clinical practice, endoscopy is reserved for evaluating patients with alarm symptoms, suspected GERD complications and surveillance for Barrett's oesophagus in patients with chronic reflux complaints.…”
Section: Upper Endoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…In referral centres, about 50% of patients will have oesophagitis, but in primary care and the general population, the rate of oesophagitis is more in the range of 48 Most patients with oesophagitis have mild LA Grade A-B disease and only 10% have the more severe LA Grade C-D oesophagitis. 42 Endoscopy can also evaluate complications of GERD, such as peptic strictures and Barrett's oesophagus, and is recommended if patients have 'alarm symptoms', such as progressive dysphagia, weight loss or iron deficiency anaemia. 42 In routine clinical practice, endoscopy is reserved for evaluating patients with alarm symptoms, suspected GERD complications and surveillance for Barrett's oesophagus in patients with chronic reflux complaints.…”
Section: Upper Endoscopymentioning
confidence: 99%
“…42 Endoscopy can also evaluate complications of GERD, such as peptic strictures and Barrett's oesophagus, and is recommended if patients have 'alarm symptoms', such as progressive dysphagia, weight loss or iron deficiency anaemia. 42 In routine clinical practice, endoscopy is reserved for evaluating patients with alarm symptoms, suspected GERD complications and surveillance for Barrett's oesophagus in patients with chronic reflux complaints. 43 Over the years, oesophageal biopsies have had a varying role in the evaluation of GERD.…”
Section: Upper Endoscopymentioning
confidence: 99%
“…in management were also made. UGIE had a greater clinical impact on decision making in male patients with alarm symptoms in this study, so the authors concluded that this was the group most likely to benefit from UGIE [41]. …”
Section: Diagnosis and Diagnostic Methodsmentioning
confidence: 99%
“…Wo et al [41] recently investigated the clinical impact of endoscopy in 206 patients with a clinical diagnosis of reflux disease referred for UGIE. They divided them into those with alarm symptoms (n = 124) compared to those with persistent heartburn despite therapy (n = 82).…”
Section: Diagnosis and Diagnostic Methodsmentioning
confidence: 99%
“…A recent study [15] has shown that this examination does not provide any advantage in the selection of the best dosing of PPIs in GORD patients. Oesophago-gastric pH testing on medication has a limited role in helping us to elucidate the reasons for PPI failure, because the majority of these patients have a normal test [16] .…”
mentioning
confidence: 99%